Localised Gingival Overgrowth in Patient taking Amlodipine - Rijal, Arjun Hari; Dhami, Bhageshwar; Pandey, Nashib; Aryal, Deepa; Neupane, Kamana (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Gingival enlargement is an increase in the size of gingiva. It is one of the side effects of systemic administration of antihypertensives, anticonvulsants, and immunosuppressants. Amlodipine, a new third-generation dihydropyridine, very useful in middle-aged to older aged patients for various cardiovascular conditions can cause gingival enlargement. Treatment modalities for drug induced gingival enlargement include removal of local irritating factors, meticulous plaque removal and drug substitution after consultation with a physician. This article reports an amlodipine induced gingival enlargement and its treatment in a 40 years old hypertensive male patient.